IMPLEMENTING RESTFUL WEB SERVICE IN MENTOR SEARCH SYSTEM WITH AGILE SCRUM METHODOLOGY - Fandy Indra Pratama; Avira Budianita; Akhmad Pandhu Wijaya; Haikal Makin Syaifudin; Tegar Widya Mustofa (STMIK Royal, 2023)
Abstract: The rapid development of technology makes stakeholders need easy and fast services. One of them is an easy and fast tutor search service. Parents who have a very busy life and school materials that develop very rapidly make parents less able to help their children learn at home so parents need a solution in the form of an information system to facilitate the search for tutors. In the development of this information system adopts by combining the architecture of the model view controller (MVC) and restful web service because development using the architecture is very easy, fast and can be developed into multi platforms. Then in the development of this system using the Agile Scrum Methodology approach which is able to complete system development very quickly and organized. Regular communication in this Scrum approach makes the team feel comfortable because each member knows each other's progress process and obstacles. So that the achievements of each target can always be controlled and completed. So that the creation of an information system for the search for tutors is on target and can be used by the public. Keywords: Agile, Agile Scrum Methodology, Information System, restful web service Abstrak: Pesatnya perkembangan teknologi membuat stakeholder membutuhkan pelayanan yang mudah dan cepat. Salah satunya adalah layanan pencarian guru les yang mudah dan cepat. Orang tua yang memiliki kehidupan yang sangat sibuk dan materi sekolah yang berkembang sangat pesat membuat orang tua kurang bisa membantu anaknya belajar di rumah sehingga orang tua membutuhkan solusi berupa sistem informasi untuk memudahkan pencarian tutor. Dalam perkembangannya sistem informasi mengadopsi dengan menggabungkan arsitektur model view controller (MVC) dan restful web service karena pengembangan menggunakan arsitektur tersebut sangat mudah, cepat dan dapat dikembangkan menjadi multi platform. Kemudian dalam pengembangan sistem ini menggunakan pendekatan Agile Scrum Methodology yang mampu menyelesaikan pengembangan sistem dengan sangat cepat dan terorganisir. Komunikasi yang teratur dalam pendekatan Scrum ini membuat tim merasa nyaman karena setiap anggota saling mengetahui proses kemajuan dan hambatan masing-masing. Sehingga capaian setiap target dapat selalu terkontrol dan selesai. Serta terciptanya sistem informasi pencarian tutor tepat sasaran dan dapat digunakan oleh masyarakat Kata kunci: Agile, Agile Scrum Methodology, Sistem Informasi, restful web service